Cardiovascular Manifestations in Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with COVID-19 According to Age - Claudia Campanello; Claudia Mercuri; Maria Derchi; Gianluca Trocchio; Alessandro Consolaro; Roberta Caorsi; Angelo Ravelli; Alessandro Rimini; Maurizio Marasini; Marco Gattorno (Children, 2022)
Cardiac involvement in multisystem inflammatory syndrome in children (MIS-C) associated with coronavirus-19 disease is often observed with a high risk of heart failure. The aim is to describe cardiovascular involvement, management and early outcome in MIS-C by comparing cardiovascular manifestations in children younger and older than 6 years old. This retrospective observational study included 25 children with MIS-C, admitted to a single pediatric center between March 2020 and September 2021. The median age was 5 years (13 patients under 6 years and 12 over 6 years); coronary artery abnormalities were observed in 77% of preschoolers, with small and medium aneurysms in half of the cases and two cases of mild ventricular dysfunction. School-age children presented myopericardial involvement with mild to moderate ventricular dysfunction in 67% of cases, and two cases of transient coronary dilatation. There was a significant NT-pro-BNP and inflammatory markers increase in 25 of the patients, and mild elevation of troponin I in 9. All patients were treated with intravenous immunoglobulin and corticosteroids, and 8 with anakinra. None of the patients needed inotropes or intensive care unit admission. Our study shows the frequent cardiovascular involvement in MIS-C with a peculiar distribution, according to different age group: coronary artery anomalies were more frequent in the younger group, and myopericardial disease in the older one. A prompt multitarget, anti-inflammatory therapy could probably contribute to a favorable outcome.